Pengaruh Struktur Modal, Kondisi Ekonomi (Inflasi), Dan Risiko Bisnis Terhadap Kinerja Keuangan Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011 - 2015 - Fitri Cinta Utami, Fitri Cinta Utami; Imronudin, S.E, M.Si, Ph.D, Imronudin, S.E, M.Si, Ph.D; Farid Wajdi, Drs., M.M.,Ph.D, Farid Wajdi, Drs., M.M.,Ph.D (2017)
The purposes of this study is to analyze the effect of capital structure, economic condition (inflation), and business risk to financial performance. The samples included 63 companies listed in Indonesian Stock Exchange in 2011 - 2015. The sampling technique used purposive sampling. Capital structure, inflation, and business risk as independent variables. While the dependent variable financial performance proxy with Return On Aseets (ROA), Return On Equity (ROE), Earning Per Share (EPS), and Tobin's Q. This Analysis using multiple linear regression. The result of research showed that the capital structure significantly affect the financial performance if used Return On Aseets (ROA) as a proxy, but if used Return On Equity (ROE), Earning Per Share (EPS), and Tobin's Q shows that a capital structure did not sifnificantly affect the financial performance. Another result of this research showed that inflation significantly affect the financial performance if used Earning Per Share (EPS) as a proxy, but if used Return On Assets (ROA), Return On Equity (ROE), Tobin's Q shows that inflation did not significantly affect the financial performance. While the results of subsequent research showed that the business risk does not significantly affect the financial performance if used Earning Per Share (EPS) as a proxy, but if used Return On Assets (ROA), Return On Equity (ROE), Tobin's Q shows that business risk did significantly affect the financial performance.